2008
DOI: 10.1155/2008/305859
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Regulatory T Cell Function of HumanCD25+CD4+T Cells from Thymocytes, Cord Blood, and Adult Peripheral Blood

Abstract: CD25+CD4+ regulatory T cells suppress T cell activation and regulate multiple immune reactions in in vitro and in vivo studies. To define the regulatory function of human CD25+CD4+ T cells at various stages of maturity, we investigated in detail the functional differences of CD25+CD4+ T cells from thymocytes, cord blood (CB), and adult peripheral blood (APB). CB CD25+CD4+ T cells displayed low-FOXP3 protein expression level and had no suppressive activity. In contrast, CD25+CD4+ T cells from thymocytes or APB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 39 publications
4
36
0
Order By: Relevance
“…These data together with observations of lower frequency of FOXP3 ϩ T cells in cord blood may explain previous contradictory results regarding the suppressive function of cord Treg. Cells that have been isolated with anti-CD25 coated magnetic beads have had weaker suppressive function than CD4 ϩ CD25 ϩ CD127 low T cells isolated by flow cytometry (6,7,35,36). This may not be surprising because ϳ90% percent of the CD4 ϩ CD25 ϩ CD127 low have been shown to express FOXP3 (37, 38), while we observed that only 28% of the CD4 ϩ CD25 ϩ T cells and 47% of the CD4 ϩ CD25 high T cells in cord blood expressed FOXP3.…”
Section: Foxp3mentioning
confidence: 99%
“…These data together with observations of lower frequency of FOXP3 ϩ T cells in cord blood may explain previous contradictory results regarding the suppressive function of cord Treg. Cells that have been isolated with anti-CD25 coated magnetic beads have had weaker suppressive function than CD4 ϩ CD25 ϩ CD127 low T cells isolated by flow cytometry (6,7,35,36). This may not be surprising because ϳ90% percent of the CD4 ϩ CD25 ϩ CD127 low have been shown to express FOXP3 (37, 38), while we observed that only 28% of the CD4 ϩ CD25 ϩ T cells and 47% of the CD4 ϩ CD25 high T cells in cord blood expressed FOXP3.…”
Section: Foxp3mentioning
confidence: 99%
“…The total number of CD4 þ T cells can then be calculated using the total lymphocyte counts and percentages of CD4 þ T cells in various tissues [19]. Percentages of Tregs in various human tissues have also been reported [20][21][22][23][24][25][26][27], allowing us to calculate the total number of Tregs present in these tissues. Based on this analysis, over 85% human Tregs reside in the primary and secondary lymphoid tissues and fewer than 2% are in circulation.…”
Section: Introductionmentioning
confidence: 99%
“…UCB Treg cells may have a survival advantage over PB Treg cells as they have been shown to be more resistant to apoptosis than PB Treg cells [21]. Finally, we and others have demonstrated Treg cells from UCB to be able to inhibit the function of effector cells [19,22,23], while other groups have reported UCB Treg cells to have low suppressive capacity [24,25]. The required cell dose for clinical use is crucial and dictates the practicality of the cell source considered and post-isolation manipulation if required.…”
Section: Use Of Umbilical Cord Blood Regulatory T Cells For Immunothementioning
confidence: 65%